(untitled) (Conferencea, 2024)
Teaching a foreign language is considered as one of the priorities of modern education. The main purpose of learning foreign languages is to develop students’ foreign language communicative competence the ability and willingness to carry out foreign language interpersonal and intercultural communication with native speakers.